Students' satisfaction on using UiTM student's portal among students' Bachelor of Business Administrative entreprenuer at UiTM Shah Alam / Nurhijanah Ali - Ali, Nurhijanah (Faculty of Business and Management, 2013)
This chapter consist of the background of study, problem statement, research questions, research objectives, significance of study, scope of study, and definition of term of the study. It is to investigate the problem occurs in the study and whether there is a relationship between service, system, information quality and student's satisfaction.To encounter most problem in the libraries is the definition of portal from Groenewegen and Hoggard (2003). Therefore, most of researcher interested to investigate the effectiveness of Jibrary portal. Similar to research done by Masrek (2007), this study using the infamous information system success model which from Delone and Mclean (1992, 2002). The student portal effectiveness are interrelated with the information quality, system quality, services quality and user satisfaction.